2016
DOI: 10.1016/j.envsoft.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two Bayesian approaches for uncertainty quantification

Abstract: To cite this version:parameters are inferred. The results show that parameter and predictive uncertainties can be accurately assessed with both the MCMC and MCPD approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…where The case d = 11 was studied in [21] in which the authors demonstrated that the MCPD draws were faster to generate than the MCMC draws (the case d = 25 was considered in [22]). Indeed, the MCPD sampler only required around one thousand evaluations of p(x|µ 1 , µ 2 , µ 3 , C) to obtain an accurate estimate of the variables' distributions.…”
Section: Numerical Exercisesmentioning
confidence: 99%
See 3 more Smart Citations
“…where The case d = 11 was studied in [21] in which the authors demonstrated that the MCPD draws were faster to generate than the MCMC draws (the case d = 25 was considered in [22]). Indeed, the MCPD sampler only required around one thousand evaluations of p(x|µ 1 , µ 2 , µ 3 , C) to obtain an accurate estimate of the variables' distributions.…”
Section: Numerical Exercisesmentioning
confidence: 99%
“…Let us now consider another challenging problem which was also analyzed in [21]. We target the twisted Gaussian density proposed in [13] and defined as follows, 2 1 + 10, 1) and p(x i ) = N (0, 1), ∀i = 3, .…”
Section: Ten-dimensional Twisted Gaussian Target Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inoue et al [17] used electrical conductivity and matric pressure head measurements at different depths for the flow-transport inversion with the local search Levenberg-Marquardt algorithm. Recently, several Bayesian approaches, where measurements are combined with prior parameter information to provide posterior parameter distributions, have been investigated for the estimation of the unsaturated hydraulic soil parameters, among others [10,12,[18][19][20][21]. The term Bayesian is used to describe statistical inversion by considering [22]: (i) That model variables are random, (ii) that randomness describes the degree of information for their realization, and (iii) that the solution of the estimation problem is the posterior probability distribution from which several statistics can be obtained.…”
Section: Introductionmentioning
confidence: 99%